Island-like mesoporous amorphous Fe2O3 layer: surface disorder engineering for enhanced lithium-storage performance. (10th January 2016) - Wang, Hai; Yang, Hongxing; Lu, Lin
Graphical abstract: The design of the amorphous metal oxides coatings of anodes could be extended to other electrode materials of LIBs, which could provide new opportunities for the design of various electrodes in building high-performance LIBs. Highlights: Island-like mesoporous amorphous Fe2 O3 layer are obtained by a facile method. The electrochemical behavior of a-Fe2 O3 @MoO3 nanobelts are investigated. The FeCl3 .6H2 O plays a multifunctional role of the formation of amorphous Fe2 O3 layer and disordering MoO3 nanobelts. The a-Fe2 O3 @MoO3 nanobelts anode material shows good electrochemical properties. Abstract: Molybdenum trioxide (MoO3 ) nanobelt is very attractive anode electrode for LIBs because of their high theoretical capacity. To enhance the capacity and cyclic performance of MoO3 -based electrode materials of lithium ion battery (LIB), here, as a proof of concept, we report in this work a novel surface disordered engineering strategy of fabrication of island-like mesoporous amorphous Fe2 O3 layer on MoO3 nanobelts (a-Fe2 O3 @MoO3 ). The island-like mesoporous amorphous Fe2 O3 layer is obtained by direct hydrolysis of FeCl3 .6H2 O on MoO3 nanobelts assisted by low-temperature heat treatment. Here, the FeCl3 .6H2 O plays a multifunctional role of the formation of amorphous Fe2 O3 layer, disordering MoO3 nanobelts and increasing the specific surface area and porosity of MoO3 nanobelts. The as-formed amorphous Fe2 O3 layer is demonstrated to significantly improve the kinetics behavior of lithium-ion diffusion and electronic transport due to its isotropic feature during cycling. As a result, the designed anode exhibits dramatically enhanced electrochemical properties compared with individual MoO3 nanobelts and physical mixture of Fe2 O3 powdes and MoO3 nanobelts: a high initial discharge capacity of 1523 mAh g −1 at 50 mA g −1, remarkable rate capability (386 mAh g −1 at 500 mA g −1 ) and outstanding cycling performance. Our results reveal new possibilities of designing amorphous oxides layer of anode electrodes by surface disorder engineering on achieving enhanced LIBs performance.